Fenomenologi Pelaksanaan Upacara Ngaben (Pitra Yadnya) di Kota Mataram (Pendekatan Sosiologi Agama) - I Wayan Wirata (Jayapangus Press, 2022)
In the field of pitra yadnya, that the sacrificial ceremony is one of the obligations of Hindus that must be carried out, because it is considered to have noble values ​​according to Vedic literature. The pitra yadnya ceremony has the meaning of paying debts to the ancestors who have given birth to mankind, so the pitra yadnya must be carried out by Hindus. But in reality, other people forbid the implementation of Ngaben (Pitra Yadnya) such as: burning corpses, using angklung gamelan facilities, and chanting kidung (wirama) because they are considered to interfere with their daily activities. This research is a qualitative research, which aims to describe and explain the meaning of sarcasm in dialect. Berg (2001) explains that qualitative research tries to answer questions by examining various social phenomena in a place and the individuals who live in that place. The data collection techniques which is used in this study are: 1) Observation by involving researchers in the daily activities of the object under study, in addition to the researcher being able to observe the object of research comprehensively; 2). Interviews with the aim of digging up information about the challenges of the pitra yadnya ceremony; and 3) Documentation is used in this study to find documents related to the phenomenological research on the implementation of pitra yadnya in Mataram City. The results of the research on the Hindu phenomenon in the implementation of the Ngaben ceremony (Pitra Yadnya) in Mataram City are as follows: domination of power, narrow religious understanding, lack of respect for local values ​​and the impact of the phenomenon of carrying out the Ngaben ceremony (Pitra Yadnya) in Mataram City are as follows : the impact of culture, social, power, and justice.